Centrifuge modelling of screw piles for offshore wind energy foundations - Davidson, C.; Al-Baghdadi, T.; Brown, M.J.; Knappett, J.; Brennan, A.; Augarde, C.E.; Wang, L.; Coombs, W.M.; Richards, D.; Blake, A.; Ball, J. (2018)
Screw piles (helical piles) can provide a viable, cost-effective and low-noise installation alternative to increasing the size of existing foundation solutions (e.g. monopiles) to meet the demand for the advancement of offshore wind energy into deeper water. Significant upscaling of widely used onshore screw pile geometries will be required to meet the loading conditions of a jacket supported offshore wind turbine. This increase in size will lead to greater installation force and torque. This paper presents preliminary results from centrifuge tests investigating the requirements to install screw piles designed for an offshore wind energy application using specially developed equipment. Results indicate that the equipment is suitable to investigate these screw pile requirements and that significant force is required for such upscaled screw piles, with 19 MN vertical force and 7 MNm torque for the standard design. Optimisation of the screw pile geometry, reduced these forces by 29 and 11% for the vertical and rotational forces respectively.
EPrint Processing Status: Full text deposited in DRO